Faktor Perilaku Keluarga yang Berhubungan dengan Kejadian ISPA pada Balita di Wilayah Kerja UPT. Puskesmas Kampa Tahun 2024 - Mardhatillah, Dela; Syahda, Syukrianti; Syafriani, Syafriani (Evidence Midwifery Journal, 2024)
One of the health problems in babies under 5 years (toddlers) is Acute One of the health problems in babies under 5 years (toddlers) is Acute Respiratory Infection (ARI). ISPA is the main cause of death in children under five in the world. The high incidence of ARI in toddlers can be caused by family behavior. The family behavior referred to is the behavior of families who smoke, the behavior of families who use mosquito repellent, especially mosquito coils and burn rubbish. The aim of the research is to determine family behavioral factors related to the incidence of ISPA in toddlers in the UPT Working Area. Kampa Community Health Center in 2024. The design of this research was to use a cross sectional method. The research results showed that there were 65 (70.7%) respondents who had bad family smoking behavior, there were 47 (51.1%) respondents who had bad behavior in using mosquito coils, there were 48 (52.2%) respondents who had bad waste burning behavior and there were 58 (63.0%) respondents who experienced ISPA. The conclusion is that there is a relationship between family smoking behavior, the behavior of using mosquito coils and the behavior of burning rubbish with the incidence of ISPA in toddlers in the UPT Working Area. Kampa Community Health Center in 2024. It is hoped that mothers of toddlers can create a safe environment for toddlers, such as avoiding smoking, not using mosquito coils and improving waste management methods, namely avoiding burning waste to prevent the occurrence of ISPA.